2005
DOI: 10.1152/ajpendo.00192.2004
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the hepatic adaptation to TPN: interaction with glycogen depletion

Abstract: In response to chronic (5 days) TPN, the liver becomes a major site of glucose disposal, removing approximately 45% (4.5 mg.kg(-1).min(-1)) of exogenous glucose. Moreover, approximately 70% of glucose is not stored but released as lactate. We aimed to determine in chronically catheterized conscious dogs the time course of adaptation to TPN and the glycogen depletion impact on early time course. After an 18-h (n = 5) fast, TPN was infused into the inferior vena cava for 8 (n = 5) or 24 h (n = 6). A third group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…The liver transitions from a site of modest glucose uptake and storage to an organ that efficiently converts glucose to lactate (9,10). This adaptation shifts the role of the liver from a site of glycogen synthesis to a major site of lactate production.…”
mentioning
confidence: 99%
“…The liver transitions from a site of modest glucose uptake and storage to an organ that efficiently converts glucose to lactate (9,10). This adaptation shifts the role of the liver from a site of glycogen synthesis to a major site of lactate production.…”
mentioning
confidence: 99%
“…Even more surprisingly, substantial liver glucose uptake occurred in the absence of hyperglycemia (ϳ6.7 mmol/l) and in only mild hyperinsulinemia (102 pmol/l) (1). Recently, our group (3) observed that the enhancement in the capacity of the liver to take up glucose (i.e., adaptive response) begins within 5 h after initiation of TPN and is nearly fully manifest by 24 h.…”
mentioning
confidence: 99%
“…AMPK was not activated by ND-4 in our study. Moreover, in our prior work, hepatic glycogen content did not alter the hepatic adaptation to nutrient delivery [15].…”
Section: Discussionmentioning
confidence: 45%